An Estimate of the Probability Density Function of the Sum of a Random Number N of Independent Random Variables. (6th April 2015) - Gifuni, Angelo; Sorrentino, Antonio; Ferrara, Giuseppe; Migliaccio, Maurizio
Abstract : A new estimate of the probability density function (PDF) of the sum of a random number of independent and identically distributed (IID) random variablesX i  ( i = 1,   2,   …,   N ) is shown. The sum PDF is represented as a sum of normal PDFs weighted according to theN PDF. The analytical model is verified by numerical simulations. The comparison is made by the Chi-Square Goodness-of-Fit test.